ANALISIS KESALAHAN SISWA SMP DALAM MENYELESAIKAN SOAL MATERI SEGIEMPAT BERDASARKAN TEORI NOLTING - Sukmawati, Suci; Amelia, Risma (IKIP Siliwangi, 2020)
The purpose of this research is to know the types of mistakes made by students in solving the problem of building a flat rectangle. This type of research is a qualitative descripive. With a research sample of 9 grade VII students taken randomly. The problem is about the instrument used in the connection capability test in the form of 5 rounds of essay. Methods performed using qualitative descriptive. Based on the data analysis obtained as much as 11.1% of students doing careless errrors (Ca), 33.3% of students made the error Concept errors (Co), 22.2% of students made a mistake application errors (Ap), 22.2% of students made a mistake Test Taking Errors (Te). It means that the whole student still feels difficulties in resolving the problem relating to the concept of a rectangular flat build.